Stool carriage of CTX-M/CMY-producing Salmonella enterica in a Chinese tertiary hospital in Shenzhen, China - Wang, Jing; Dong, Zi-Han; Zhou, Xian-Yuan; Ma, Qin-Chun; Wang, Zhen-Yu; Lin, Dachuan; Huang, Ying-Feng; Zhang, Chi; Jiao, Xinan; Li, Deng; Li, Qiuchun (Frontiers in Cellular and Infection Microbiology, 2025)
Salmonellosis, caused by non-typhoidal Salmonella, is a common foodborne gastrointestinal infection. Third-generation cephalosporins are recommended as the first-line treatment for Salmonella infections. Our study aimed to investigate the molecular epidemiology, antimicrobial resistance, and the transmission of extended-spectrum β-lactamases (ESBL) genes in 96 clinical Salmonella isolates collected between 2020 and 2022 at a tertiary hospital in Shenzhen, China. We performed antimicrobial susceptibility testing and whole-genome sequencing to identify serotypes, multilocus sequence typing, antimicrobial resistance genes in these isolates, and the genetic structures of the blaCTX-M/blaCMY genes. Seventeen Salmonella serotypes were identified, with S. 4,[5],12:i:- (37.5%) being the most common, followed by S. Enteritidis (15.63%), S. Typhimurium (14.58%), S. London (7.29%), and S. Rissen (5.21%). MLST analysis revealed 19 distinct sequence types (STs), with ST34 being the most prevalent (36.46%), followed by ST11 (15.63%) and ST19 (13.54%). Antimicrobial resistance testing showed those isolates had high levels of resistance to ampicillin (72.92%) and tetracycline (71.88%), with 70.83% of isolates as multidrug-resistant (MDR). Three blaCTX-M genes (blaCTX-M-14,blaCTX-M-55, and blaCTX-M-65) and blaCMY-2 were identified among 18 cefotaxime-resistant strains, of which one and 12 isolates successfully transferred blaCMY or blaCTX-M to E. coli C600 via conjugation, respectively. The blaCTX-M/blaCMY-2-carrying contigs in nine Salmonella isolates ranged from 2,156 to 164,862 bp, were located either on the chromosome (n=1) or plasmids (IncI1, IncK1, IncA/C) (n=9), and the blaCTX-M/blaCMY-2 genes were associated with ISEcp1. Our study demonstrates the diversity of MDR Salmonella serotypes in clinical isolates, and highlights the role of plasmids and mobile genetic elements in the horizontal transfer of blaCTX-M/blaCMY, emphasizing the need for continuous surveillance of Salmonella in clinical samples.